2000
DOI: 10.1093/ajcn/71.6.1545
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the conversion of β-carotene to vitamin A in women measured by using a double-tracer study design

Abstract: Background: Blood ␤-carotene and vitamin A responses to oral ␤-carotene are variable in humans. Some individuals are characterized as responders and others as low-or nonresponders. A better understanding of the conditions that produce the variability is important to help design public health programs that ensure vitamin A sufficiency. Objective: Our objective was to assess variability in absorption and conversion of ␤-carotene to vitamin A in vivo in humans by using a novel double-tracer [hexadeuterated (D 6 )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
42
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 44 publications
(69 reference statements)
12
42
1
1
Order By: Relevance
“…The study clearly indicated that there is lower bioconversion of β-carotene to retinol with a higher dose of β-carotene. The lower dose of β-carotene used (6 mg) was closer to the amounts obtained from an average vegetablecontaining diet and less than one-third of that used by Lin et al 68 and Hickenbottom et al 69 . Thus the study of Tang et al 70 suggests that bioconversion of β-carotene to retinol is better from smaller doses and would support the view that the method used by van Lieshout et al 65 has advantages over the other methods used in measuring the bioefficacy of β-carotene.…”
Section: Bioconversion To Retinol Of Pharmacological and Physiologicasupporting
confidence: 50%
See 2 more Smart Citations
“…The study clearly indicated that there is lower bioconversion of β-carotene to retinol with a higher dose of β-carotene. The lower dose of β-carotene used (6 mg) was closer to the amounts obtained from an average vegetablecontaining diet and less than one-third of that used by Lin et al 68 and Hickenbottom et al 69 . Thus the study of Tang et al 70 suggests that bioconversion of β-carotene to retinol is better from smaller doses and would support the view that the method used by van Lieshout et al 65 has advantages over the other methods used in measuring the bioefficacy of β-carotene.…”
Section: Bioconversion To Retinol Of Pharmacological and Physiologicasupporting
confidence: 50%
“…The same method was used in both studies and the main objective was to assess variability of β-carotene conversion to retinol, in 11 well-nourished women 68 and 11 men. 69 The tracers used were hexadeuterated ( 2 H 6 ) retinyl acetate and 2 H 6 β-carotene.…”
Section: Conversion Of β-Carotene To Retinol In Healthy Well-fed Amermentioning
confidence: 99%
See 1 more Smart Citation
“…Low converters have a low postprandial conversion efficiency after supplementation, reflected by the retinyl ester/ b-carotene ratio measured in the chylomicron fraction [7]. Approximately, 45% of the western population can be classified as low converter [30,47]. It has been established that conversion efficiency is depending at least in part on the vitamin A status [57], which is explained by the existence of a negative feedback of RA on BCMO1 mRNA expression [3,66].…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%
“…It has been established that conversion efficiency is depending at least in part on the vitamin A status [57], which is explained by the existence of a negative feedback of RA on BCMO1 mRNA expression [3,66]. Besides, many studies have highlighted the huge interindividual variability in conversion efficiency, with a coefficient of variation being as high as 221% [7,12,30,47]. Furthermore, according to [77] who investigated the kinetics of a labelled b-carotene dose [77], low responders would also display a lower conversion efficiency compared to normal responders (Fig.…”
Section: Carotenoid Oxygenasesmentioning
confidence: 99%